The Relationship Between Climate Elements and Electric Power Production in Southern Iraq - Imad Kareem Al-Majidi , Researcher. Ali; Abdul Rashid Al-Sharifi, Prof. Dr. Rashid; Mia Rudain , Assist. Lect . Dr. Waleed (Basra studies journal, 2026)
The electricity sector in southern Iraq represents one of the key pillars of development; however, it faces increasing operational challenges due to the direct impact of climatic factors alongside the continuously growing demand. This study aims to examine the statistical relationship between the main climatic elements—temperature, relative humidity, and wind speed—on one hand, and electricity production in the southern region on the other, during the period 2012–2023. The study relied on official climatic and electricity production data and employed statistical tools, including Pearson correlation and simple and multiple linear regression, to measure the strength and direction of the relationships. The results indicated that increases in temperature and humidity negatively affected generation efficiency in thermal and gas power plants, while wind contributed to improving some generation patterns. The study emphasizes the importance of integrating climatic factors into power plant operation and maintenance plans and exploring technical alternatives to mitigate their adverse effects.